Alphasatellitidae: a new family with two subfamilies for the classification of geminivirus- and nanovirus-associated alphasatellites - Briddon, Rob W.; Martin, Darren P.; Roumagnac, Philippe; Navas-Castillo, Jesús; Fiallo-Olivé, Elvira; Moriones, Enrique; Lett, Jean-Michel; Zerbini, F. Murilo; Varsani, Arvind (Archives of virology, 2018)
Nanoviruses and geminiviruses are circular, single stranded DNA viruses that infect many plant species around the world. Nanoviruses and certain geminiviruses that belong to the Begomovirus and Mastrevirus genera are associated with additional circular, single stranded DNA molecules (~ 1-1.4 kb) that encode a replication-associated protein (Rep). These Rep-encoding satellite molecules are commonly referred to as alphasatellites and here we communicate the establishment of the family Alphasatellitidae to which these have been assigned. Within the Alphasatellitidae family two subfamilies, Geminialphasatellitinae and Nanoalphasatellitinae , have been established to respectively accommodate the geminivirus- and nanovirus-associated alphasatellites. Whereas the pairwise nucleotide sequence identity distribution of all the known geminialphasatellites (n = 628) displayed a troughs at ~ 70% and 88% pairwise identity, that of the known nanoalphasatellites (n = 54) had a troughs at ~ 67% and ~ 80% pairwise identity. We use these pairwise identity values as thresholds together with phylogenetic analyses to establish four genera and 43 species of geminialphasatellites and seven genera and 19 species of nanoalphasatellites. Furthermore, a divergent alphasatellite associated with coconut foliar decay disease is assigned to a species but not a subfamily as it likely represents a new alphasatellite subfamily that could be established once other closely related molecules are discovered.